2015
DOI: 10.3111/13696998.2015.1067622
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of exenatide twice daily (BID) vs insulin glargine once daily (QD) as add-on therapy in Chinese patients with Type 2 diabetes mellitus inadequately controlled by oral therapies

Abstract: Compared with insulin glargine QD, exenatide BID as add-on therapy to OAD is a cost-effective treatment in Chinese patients inadequately controlled by OAD treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The discrepancies may be related to the differences in BMI‐related prescription costs and the economic evaluation model used, as previous studies were based on an IMS CORE diabetes model which does not include a variable for BMI‐related prescription costs, unlike the Cardiff Diabetes Model. A previous study using the Cardiff Diabetes Model in China also confirmed that exenatide twice daily was superior to insulin glargine once daily; however, one study has also shown that exenatide twice daily does not represent a cost‐effective treatment option for patients with T2DM compared with insulin glargine once daily . This result could potentially be attributed to the exclusion of cost and utility changes associated with BMI changes in that study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The discrepancies may be related to the differences in BMI‐related prescription costs and the economic evaluation model used, as previous studies were based on an IMS CORE diabetes model which does not include a variable for BMI‐related prescription costs, unlike the Cardiff Diabetes Model. A previous study using the Cardiff Diabetes Model in China also confirmed that exenatide twice daily was superior to insulin glargine once daily; however, one study has also shown that exenatide twice daily does not represent a cost‐effective treatment option for patients with T2DM compared with insulin glargine once daily . This result could potentially be attributed to the exclusion of cost and utility changes associated with BMI changes in that study.…”
Section: Discussionmentioning
confidence: 66%
“…The model uses the 68 or 82 risk equations from the UK Prospective Diabetes Study (UKPDS) to estimate the risk of clinical endpoints and predict the occurrence of diabetes‐related complications and mortality . The present study used the UKPDS 68‐equation model as these equations are widely implemented in diabetes modelling and are extensively tested and validated compared with the UKPDS 82 equations . A sensitivity analysis was performed using the latter model.…”
Section: Methodsmentioning
confidence: 99%
“…GLP1s were not cost-effective compared with insulins in UMICs (n=3 53–55 ) with INB p of US$35 372.19 (95% CI US$−9955.53 to US$80 899.91, I 2 =91.3%), see online supplementary figure 9B . A funnel plot and Egger’s test (coefficient=3.40, SE=0.07, p=0.013) showed asymmetry; a contour-enhanced funnel plot suggested that this may be due to both heterogeneity and missing studies (see online supplementary figure 13A, B ).…”
Section: Resultsmentioning
confidence: 96%
“…Among the studies looking at GLP1s versus insulins, 24 and 3 53–55 were from HICs and UMICs. One study 51 had an outlier INB (based on scenario 5) and was excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of real-world effectiveness and cost data into CEA complements the evidence derived from clinical trials and ensures that the results will be relevant for the real-life healthcare decision-making context [7,8]. However, most CEAs of GLP-1RA versus insulin therapy for T2D patients have been model-based (e.g., Markov modeling simulation) analyses that used data mainly derived from clinical trials that assessed short-term drug efficacy in terms of biomarker changes among highly selective and homogenous patient populations [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Such approaches greatly affect the generalizability of study results to real-world settings and raise concerns about the validity of projecting the results to long-term outcomes.…”
mentioning
confidence: 99%